2007
DOI: 10.2215/cjn.02410706
|View full text |Cite
|
Sign up to set email alerts
|

A Standard, Noninvasive Monitoring of Hematocrit Algorithm Improves Blood Pressure Control in Pediatric Hemodialysis Patients

Abstract: Accurate dry weight assessment is difficult in pediatric hemodialysis patients but is essential to prevent chronic fluid overload, hypertension, and cardiovascular morbidity. A noninvasive monitoring (NIVM) of hematocrit-guided ultrafiltration algorithm was studied prospectively in 20 pediatric hemodialysis patients. The algorithm targeted the first 50% of total goal ultrafiltration to be removed during the first hour of dialysis with a maximum blood volume change of 8 to 12% per hour. The second 50% was remov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
2
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(35 citation statements)
references
References 30 publications
1
30
2
2
Order By: Relevance
“…106 It is possible that the latter benefit is, in part, related to diminished use of antihypertensive medication. Accordingly, monthly monitoring of RPV and home BP may offer an attractive way to assess the adequacy of volume control among HD patients.…”
Section: Dry Weight and Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…106 It is possible that the latter benefit is, in part, related to diminished use of antihypertensive medication. Accordingly, monthly monitoring of RPV and home BP may offer an attractive way to assess the adequacy of volume control among HD patients.…”
Section: Dry Weight and Outcomesmentioning
confidence: 99%
“…193 A blood volume monitoring protocol in a multicenter study demonstrated improved control of hypertension with decreased need for antihypertensive medications, although no significant change in postdialysis weight was seen. 106 In pediatric PD patients, a plasma atrial natriuretic peptide level .3.0 nmol/L was felt to reflect hypervolemia on one study, 187 but this finding has not yet been replicated.…”
Section: Hypertension In Pediatric Dialysis Patientsmentioning
confidence: 99%
“…without symptomatic intradialytic hypotension) that allows the patient to maintain a normal interdialytic blood pressure, ideally without the use of antihypertensive medications [3,6]. Despite technological advances in intradialytic relative plasma volume monitoring [9,10] and bioimpedance analysis [11,12], the assessment of dry weight in children remains challenging [6]. However, these new technical tools provide objective measures to corroborate the clinical assessment of dry weight by the dialysis team.…”
Section: Assessing Dry Weight and Idwg In Children On Chronic Dialysismentioning
confidence: 99%
“…To achieve euvolaemia many nephrologists prescribe high ultrafiltration rates [17], especially if the patient appears to tolerate it [3,8]. A patient's tolerance to a higher ultrafiltration rate depends on many factors, including maintaining normal haemoglobin levels, the use of bicarbonate dialysate buffe r, h i g h e r d i a l y s a t e s o d i u m c o n c e n t r a t i o n [ 5 ] , haemodiafiltration technology [18], ultrafiltration or sodium profiling, lowering dialysate temperature and on-line blood volume monitoring [9,10], and has dramatically improved over the last decades [6]. Nonetheless, even a well-tolerated high ultrafiltration rate, such as >1.24 % body weight loss per hour in adults, is associated with greater mortality [19].…”
Section: Managing Idwg: Safely Achieving the Desired Ultrafiltrationmentioning
confidence: 99%
“…Studies among hemodialysis patients in adults and children suggest that managing intradialytic RPV may reduce the number of hospital admissions due to fluid overload (14,19), improve BP control, and decrease hypotension-associated dialysis symptoms (20). It is possible that the latter benefit is, in part, related to diminished use of antihypertensive medication.…”
Section: Dry-weight and Outcomesmentioning
confidence: 99%